2002
DOI: 10.1016/s0925-4439(01)00085-0
|View full text |Cite
|
Sign up to set email alerts
|

Presence of BRCA1 and BRCA2 proteins in human milk fat globules after delivery

Abstract: We evaluated BRCA1 and BRCA2 oncosuppressor protein expression in 26 milk samples in women just after delivery. The quantification of BRCA1 and BRCA2 proteins was performed in isolated milk fat globules using an affinity chromatography strategy. The amounts of BRCA1 and BRCA2 proteins were found to be similar. We explained the presence of BRCA1 and BRCA2 proteins in human milk fat globules by the fact that they are formed by exocytosis of lipids from epithelial cells of the mammary gland and are enveloped by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…We displayed the specificity of the anti-BRCA1 and anti-BRCA2 polyclonal antibodies by competition with the synthetic peptides used to generate the antibodies. A complete displacement of the equilibrium was obtained in each case demonstrating the specificity of the antibodies (data not shown) (Hizel et al, 1999;Vissac et al, 2001Vissac et al, , 2002.…”
Section: Discussionmentioning
confidence: 78%
“…We displayed the specificity of the anti-BRCA1 and anti-BRCA2 polyclonal antibodies by competition with the synthetic peptides used to generate the antibodies. A complete displacement of the equilibrium was obtained in each case demonstrating the specificity of the antibodies (data not shown) (Hizel et al, 1999;Vissac et al, 2001Vissac et al, , 2002.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, they demonstrated the presence of the onco-suppressor BRCA1 protein in bovine and human MFGM (Spitsberg & Gorewit, 1998). Vissak et al (2002) detected BRCA1 and BRCA2 in extracts obtained from human and bovine MFGM using affinity chromatography. Both the BRCA2 and BRCA1 proteins are involved in DNA repair processes, although BRCA2 has an additional function as one of the direct regulators of cytokinesis (Daniels, Wang, Lee, & Venkitaraman, 2004).…”
Section: Phospholipidsmentioning
confidence: 99%
“…Interestingly, some authors [7,58] have demonstrated the presence of the onco-suppressors breast related cancer antigens 1/2 (BRCA1 and BRCA2) in human and bovine MFGM. These two onco-suppressors are involved in DNA repair processes [7].…”
Section: Major Mfgm Proteinsmentioning
confidence: 99%